Profiles of worldwide government leaders. - Worldwide Government Directories, Inc. (Bethesda, MD Worldwide Government Directories, Inc., 1995)
Annual
Keywords: Cabinet officers -- Biography -- Periodicals; Cabinet officers -- Directories; Heads of state -- Biography -- Periodicals; Heads of state -- Directories; Statesmen -- Biography -- Periodicals; Statesmen -- Directories